Efficacy and safety outcomes of recanalisation procedures in patients with acute symptomatic pulmonary embolism: systematic review and network meta-analysis. Issue 5 (13th November 2017) - Jimenez, David; Martin-Saborido, Carlos; Muriel, Alfonso; Zamora, Javier; Morillo, Raquel; Barrios, Deisy; Klok, Frederikus A; Huisman, Menno V; Tapson, Victor; Yusen, Roger D
Abstract : Background: We aimed to review the efficacy and safety of recanalisation procedures for the treatment of PE. Methods: We searched PubMed, the Cochrane Library, EMBASE, EBSCO, Web of Science and CINAHL databases from inception through 31 July 2015 and included randomised clinical trials that compared the effect of a recanalisation procedure versus each other or anticoagulant therapy in patients diagnosed with PE. We used network meta-analysis and multivariate random-effects meta-regression to estimate pooled differences between each intervention and meta-regression to assess the association between trial characteristics and the reported effects of recanalisation procedures versus anticoagulation. Results: For all-cause mortality, there were no significant differences in event rates between any of the recanalisation procedures and anticoagulant treatment (full-dose thrombolysis: OR 0.60; 95% CI0.36 to 1.01; low-dose thrombolysis: 0.47; 95% CI 0.14 to 1.59; and catheter-associated thrombolysis: 0.31; 95% CI 0.01 to 7.96). Full-dose thrombolysis increased the risk of major bleeding (2.00; 95% CI 1.06 to 3.78) compared with anticoagulation. Catheter-directed thrombolysis was associated with the lowest probability of dying (surface under the cumulative ranking curve (SUCRA), 0.67), followed by low-dose thrombolysis (SUCRA, 0.66) and full-dose thrombolysis (SUCRA, 0.55). Similarly, low-dose thrombolysis was associated with the lowest probability of major bleeding (SUCRA, 0.61), followed by catheter-directed thrombolysis (SUCRA, 0.54) and full-dose thrombolysis (SUCRA, 0.17). The results were similar in sensitivity analyses based on restricting only to studies in haemodynamically stable patients with PE. Conclusions: In the treatment of PE, recanalisation procedures do not seem to offer a clear advantage compared with standard anticoagulation. Low-dose thrombolysis was associated with the lowest probability of dying and bleeding. Trial registration number: PROSPERO CRD42015024670.